(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
Shifts in some cardiac hemodynamic parameters were studied in students during a 15-minute cycle ergometer load attended with cold inhalation of clove essential oil. It is shown that the use of essential oil of cloves contributes to the alignment of shifts in the level of functional indicators of students, by increasing the adaptive capacity of the organism. Essential oil of cloves causes a decrease of “physiological cost” of physical activity performed by students by strengthening the economization processes of functional systems activity. Curing an increase in the sympathetic effects on the body, induced by physical activity, the oil of cloves contributes to the rapid restoration of the functional state of the body in the nearest post-load period. As a control, indicators of the functional state and cardiac hemodynamics of students who, during bicycle ergometer load, were not subjected to the corrective influence of the essential oil of cloves, were used.